2019
DOI: 10.1111/nyas.14196
|View full text |Cite
|
Sign up to set email alerts
|

Nrf2–Keap1 pathway–mediated effects of resveratrol on oxidative stress and apoptosis in hydrogen peroxide–treated rheumatoid arthritis fibroblast‐like synoviocytes

Abstract: Resveratrol (Res) is a polyphenolic compound that has a variety of biological functions and activities. This study aimed to explore the mechanisms of the antioxidant and proapoptotic effects of Res in H2O2‐treated rheumatoid arthritis fibroblast‐like synoviocytes (RA‐FLSs) by the Nrf2–Keap1 signaling pathway. We found that 5 µM H2O2 promoted cell proliferation and increased intracellular reactive oxygen species (ROS) and malondialdehyde (MDA) content in RA‐FLSs. However, Res could reverse these effects in 5 µM… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

4
48
0
1

Year Published

2019
2019
2023
2023

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 80 publications
(53 citation statements)
references
References 58 publications
4
48
0
1
Order By: Relevance
“…Our data show that resveratrol down‐regulated the levels of p65‐NF‐κB protein expression in AIA animals similar to other studies, which demonstrated that resveratrol suppresses inflammation by down‐regulating NF‐κB activation. [ 40,44 ] Remarkably, our data described a strong positive correlation between p62 and p65‐NF‐κB. In this sense, it has been described how NF‐κB induces expression of p62 and as defective autophagy results in accumulation of p62, which can activate NF‐κB.…”
Section: Discussionsupporting
confidence: 67%
“…Our data show that resveratrol down‐regulated the levels of p65‐NF‐κB protein expression in AIA animals similar to other studies, which demonstrated that resveratrol suppresses inflammation by down‐regulating NF‐κB activation. [ 40,44 ] Remarkably, our data described a strong positive correlation between p62 and p65‐NF‐κB. In this sense, it has been described how NF‐κB induces expression of p62 and as defective autophagy results in accumulation of p62, which can activate NF‐κB.…”
Section: Discussionsupporting
confidence: 67%
“…Resveratrol may be able to suppress the proinflammatory activity and may be potent in treating metabolic disorders that usually are associated with PCOS [27]. Furthermore, experimental evidence has demonstrated a protective effect of resveratrol against several conditions mediated by OS [28]. Thus, we undertook to examine the effect of resveratrol on protection of PCOS rats from ovarian fibrosis mediated by p66Shc-induced OS.…”
mentioning
confidence: 99%
“…As a consequence, the body generates an oxidative stress response to promote cell apoptosis, though pathological injury may still result (32). It is established that the ROS-mediated oxidative stress is a key inducer of cell apoptosis (33). ROS may also serve as a messenger in cells that is able to promote the activation of apoptosis to indirectly cause cell injury (34).…”
Section: Discussionmentioning
confidence: 99%